Weapons of words: intertextual competition in Babylonian poetry : a study of Anzū, Enūma eliš, and Erra and Išum - Wisnom, Laura Selena, 1986- (Culture and History of the Ancient Near East;, 2020)
In Weapons of Words: Intertextual Competition in Babylonian Poetry Selena Wisnom offers an in-depth literary study of three poems central to Babylonian culture: Anzû, Enūma eliš, and Erra and Išum . Fundamentally interconnected, each poem strives to out-do its predecessors and competes to establish its protagonist, its ideals, and its poetics as superior to those that came before them. The first of its kind in Assyriology, Weapons of Words explores the rich nuances of these poems by unravelling complex networks of allusion. Through a sophisticated analysis of literary techniques, Selena Wisnom traces developments in the Akkadian poetic tradition and demonstrates that intertextual readings are essential for a deeper understanding of Mesopotamian literature.